Track of HSMS Sophia tracing the extent of navigable water along the main northern ice between Spitzbergen and Greenland September 1868 : also showing the nature of the ice and temperature and depth of the sea ([S.l.], 1870)
Kartta kuuluu A. E. Nordenskiöldin kokoelmaan